Konstruksi Hukum Perkawinan Poligami di Indonesia (Prespektif Hukum Feminis) - Shinta Dewi Rismawati (MUWAZAH : jurnal kajian gender, 2017)
The paper criticizes the construction of law, the existing legal arrangements concerning polygamous marriage in the perspective of legal feminism. The argument is that the legal construction of polygamous marriages in Indonesia is in fact not value-free, ambitious and adheres to a conventional patriarchal paradigm. The findings and analysis show that, Law Number 1 Year 1974 on Marriage is not value-free, ambiguous and gray, thus perpetuating the uncertainty in marriage law. The marriage law of conventional patriarchal paradigm just legitimizes husband's sexuality for polygamy by placing steorotif on women as her ordinate platform.